2014
DOI: 10.1021/jf4049512
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Activity of Natural Food Additive Triterpenoids as Influenced by Protein

Abstract: Triterpenoids were thought to be biologically ineffective for a very long time, but aggregating proof on their widely ranging pharmacological activities paired with a dubious toxicity portrait has motivated regenerated attraction for human health and disease. In the current contribution, our central goal was to integratively dissect the biointeraction of two typical triterpenoids, ursolic acid and oleanolic acid, by the most fundamental macromolecule bovine serum albumin (BSA) by employing molecular modeling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 59 publications
(78 reference statements)
2
19
0
Order By: Relevance
“…Little alteration in the fluorescence lifetime of BSA was detected upon the addition of DMA. Similar findings have been reported in literature for several drugs associated with BSA [16,37].…”
Section: Time-resolved Fluorescence and Angular Anisotropy Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…Little alteration in the fluorescence lifetime of BSA was detected upon the addition of DMA. Similar findings have been reported in literature for several drugs associated with BSA [16,37].…”
Section: Time-resolved Fluorescence and Angular Anisotropy Studiessupporting
confidence: 92%
“…Despite the ample literature, however, little firm knowledge is available on the binding between albumin and triterpenoids [14][15][16][17], especially on structure-affinity relationship of these compounds with albumin. Clearly, an understanding of the interaction of these pharmaceuticals with albumin is needed to gain insight into their therapeutic effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum yields of fluorescence of the conjugates are lower than those of BODIPY‐FL propanoic acid ( Φ =98 for 19 vs. Φ =0.14–0.30 for compounds 24 – 32 ). The diminished fluorescence is probably caused by the static quenching between BODIPY dye and triterpenes, which is consistent with recently published data …”
Section: Resultsmentioning
confidence: 99%
“…Although they were long considered biologically ineffective, recent evidence points to the beneficial effects both of naturally occurring triterpenoids as well as of synthetic derivatives against several types of human diseases, including certain cancers [7][8][9][10]. Naturally occurring triterpenoids such as oleanolic, betulinic, ursolic and maslinic acids have shown significant pharmacological activity, and recent studies suggest a promising potential of these products as anticancer agents [8][9][10][11][12]. Also, several studies examine their interaction with serum albumins [9,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring triterpenoids such as oleanolic, betulinic, ursolic and maslinic acids have shown significant pharmacological activity, and recent studies suggest a promising potential of these products as anticancer agents [8][9][10][11][12]. Also, several studies examine their interaction with serum albumins [9,[13][14][15][16][17][18][19]. Moreover, it has recently been observed that small structural modifications in these natural substances can produce advantageous derivatives with favorable chemotherapeutic properties [12,16,20].…”
Section: Introductionmentioning
confidence: 99%